Comparing Types of Statistical Data Between Turkey (the Case Study of Istanbul) and Selected Countries for Creating Fire Strategies - Erhan Bakırcı; Buket Karatop; Sümeyye Bayındır (Doğal Afetler ve Çevre Dergisi)
Fires caused by natural factors or man-made and the losses they cause are known to have traumatic consequences for the society. The risk of disasters can be minimized when they are determined in advance and the results of the disasters become manageable. In addition to material and moral losses and socio-cultural traumas caused by disasters, especially fire disasters, the effects on the eco-system are felt more and more every day. Therefore, it can be said that fire statistics are kept and used to determine the strategies of fire statistics, especially in the countries that have high standards of social security and are technologically advanced. The strength of this chain of secure relations is possible with the establishment of learning systems. The basic factor in the creation and establishment of measurable-evaluable and taken lessons from lived data systems is the establishment of a robust, scientific and objective statistical data pool and with awareness raising. In this study, Istanbul Fire Brigade converted fires that occurred in Istanbul between 2008 and 2018 into statistical data. These statistics were compared with the fire statistics of the USA, China and EU countries. The largest and most comprehensive fire statistics database in our country is represented by the Istanbul Province Fire Statistics. Compared to the fire statistics of other countries, it was determined that there were differences in the statistical data classification and evaluation of these data. Thus, it is discussed whether the data held are suitable for creating strategies in this area with scientific studies and preventive approaches, and suggestions for improvement are presented.